2014
DOI: 10.1111/1567-1364.12155
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation ofCandida albicansto growth on sorbose via monosomy of chromosome 5 accompanied by duplication of another chromosome carrying a gene responsible for sorbose utilization

Abstract: Candida albicans, a fungus that normally inhabits the digestive tract and other mucosal surfaces, can become a pathogen in immunocompromised individuals, causing severe or even fatal infection. Mechanisms by which C. albicans can evade commonly used antifungal agents are not fully understood. We are studying a model system involving growth of C. albicans on toxic sugar sorbose, which represses synthesis of cell wall glucan and, as a result, kills fungi in a manner similar to drugs from the echinocandins class.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…S3 for other mutants). By combining analyses of MTL locus hemizygosity, which implied the loss of one Ch5, PFGE analyses of the chromosome banding patterns, which showed an unknown band migrating between Ch5 (ϳ1,295 kbp) and Ch4 (ϳ1,883 kbp) (25), and DNA-seq analyses, we concluded that the unknown band was a chromosome carrying two right arms of Ch5 (each of ϳ825.6 kbp), thus resulting in an iso-Ch5R with a total length of ϳ1,651 kbp. Because the MTL locus resides on the left arm of Ch5, iso-Ch5R has no MTL locus, and the corresponding mutants are hemizygous for the MTL locus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 for other mutants). By combining analyses of MTL locus hemizygosity, which implied the loss of one Ch5, PFGE analyses of the chromosome banding patterns, which showed an unknown band migrating between Ch5 (ϳ1,295 kbp) and Ch4 (ϳ1,883 kbp) (25), and DNA-seq analyses, we concluded that the unknown band was a chromosome carrying two right arms of Ch5 (each of ϳ825.6 kbp), thus resulting in an iso-Ch5R with a total length of ϳ1,651 kbp. Because the MTL locus resides on the left arm of Ch5, iso-Ch5R has no MTL locus, and the corresponding mutants are hemizygous for the MTL locus.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported regulation of the same phenotype in C. albicans by two different mechanisms, one of which is associated with Ch5 rearrangement and the other with gene dose. The SOU1 gene, carried on the trisomic Ch4/7b in the mutant Sor125(55), which also possesses the monosomic Ch5, can be upregulated either due to an additional copy or due to the monosomic condition of Ch5 (25).…”
Section: Fig 8 Map Of Ch5mentioning
confidence: 99%
“…Mutations in particular need to become fixed in a population, which in many fungi would mean a whole mycelium. However, fungi seem to be able to tolerate high levels of chromosomal mutations such as polyploidies and aneuploidies, particularly under stressful conditions (Cogliati et al ., ; Li et al ., ; Bennett, Forche & Berman, ; Kravets et al ., ; Gerstein & Berman, ; Berman, Wertheimer & Stone, ; Todd, Forche & Selmecki, ). From a phenotypic point of view, impairment in regulatory networks caused by chromosomic aberrations has the potential to affect signalling pathways controlling morphological complexity.…”
Section: Genome Complexitymentioning
confidence: 99%
“…In addition to monosomy of Ch5, this mutant acquired duplication of a chimeric Ch4/7b, resulting in trisomy of this chromosome (Fig. 1 a), and facilitating the Sou + phenotype [ 8 ]. Similar to Ch5, our data show that while expression of many genes on the trisomic Ch4/7b increased 1.5-fold, as expected from gene copy number, many other genes were expressed at the normal disomic or near disomic levels (C. Tucker and E. Rustchenko, unpublished observation).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomes are designated from 1 to 7 and R, on the left, as their sizes decrease from top to bottom. For the chromosome sizes, see [ 8 ]. ChR refers to the chromosome containing a cluster of tandemly repeated rDNA units.…”
Section: Introductionmentioning
confidence: 99%